2018
DOI: 10.3389/fimmu.2018.02026
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Regulation of Germinal Center Formation

Abstract: Germinal centers (GCs) are essential structures of the humoral immune response, which form in the periphery in response to T cell dependent antigens. During the GC reaction, B cells undergo critical differentiation steps, which ultimately lead to the generation of antibodies with altered effector function and higher affinity for the selected antigen. Remarkably, many of the B cell tumors have their origin in the GCs; thus, understanding how the formation of these structures is regulated or deregulated is of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(141 citation statements)
references
References 100 publications
0
134
0
Order By: Relevance
“…Interestingly, 61.5% of the changes between NBC and GCBC involved compartment activation (Figure 2C-D). As the germinal center reaction is known to be mediated by specific transcription factors (TFs) 42,43 and those may be involved in shaping the spatial organization of the genome 8,14,16 , we further explored the presence of TF binding motifs in the newly activated compartments. We identified significantly enriched motifs for MEF2 and POU families (Figure 2F and Supplementary Table 3) , which are essential TFs involved in germinal center formation 4447 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 61.5% of the changes between NBC and GCBC involved compartment activation (Figure 2C-D). As the germinal center reaction is known to be mediated by specific transcription factors (TFs) 42,43 and those may be involved in shaping the spatial organization of the genome 8,14,16 , we further explored the presence of TF binding motifs in the newly activated compartments. We identified significantly enriched motifs for MEF2 and POU families (Figure 2F and Supplementary Table 3) , which are essential TFs involved in germinal center formation 4447 .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, TFs have been described to act as the architects instructing structural changes in the genome 75 and a recent report has described that TFs are able to drive topological genome reorganizations even before detectable changes in gene expression 8 . A detailed analysis of regions that become exclusively active in GCBC as compared to any other B cell subpopulation under study revealed an enrichment in TF binding motifs of MEF2 and POU families, which have been described to play a key role in the germinal center formation 43 . In line with this important role of TFs in activating chromatin in GCBC, we also identified that…”
Section: Discussionmentioning
confidence: 97%
“…This strategy is understandable, as it provides a framework for thinking about the cell-cell and molecular events responsible for the observed response. [21][22][23][24][25] Hence, we will provide a bird's eye view of these structures to set the stage for our discussion on the key events in extrafollicular responses and how they contrast with GCbased responses. for the response in question.…”
Section: Ba S Ic Elements Of the G Erminal Center Re Ac Ti Onmentioning
confidence: 99%
“…[18][19][20] Germinal centers have been reviewed by multiple writers and from numerous angles. [21][22][23][24][25] Hence, we will provide a bird's eye view of these structures to set the stage for our discussion on the key events in extrafollicular responses and how they contrast with GCbased responses. Very early in responses induced by proteinaceous antigens activated B and T cells congregate at boundaries between T cell rich regions in the spleen or lymph node and B-cell enriched follicles.…”
Section: Antibodies B Cells Cell Differentiation Germinal Centersmentioning
confidence: 99%
“…Quantitative modelling of GCs : At the molecular level, the intracellular mechanisms associated with regulation of the B cells, T and FDCs interactions implicates more than 100 transcription factors [ 16 ], most of which interact in highly regulated non-linear networks [ 17 ], making the precise quantitative modeling of GC reaction tremendously complex. As GCs are stochastic systems that display a high level of variability even within the same lymph node of the same individual [ 18 ], mathematical models have been widely used to deepen our understanding of the cellular and molecular processes characterising these complex dynamic systems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%